Variation in species richness, composition and herpetological community structure across a tropical habitat gradient of Palawan Island, Philippines - Christian E. Supsup; Augusto A. Asis; Uldarico V. Carestia Jr; Arvin C. Diesmos; Neil Aldrin D. Mallari; Rafe M. Brown (Herpetozoa, 2020)
Information on species richness and community structure is invaluable for guiding conservation and management of biodiversity, but is rarely available in the megadiverse biodiversity conservation hotspot of Philippines – particularly for amphibians and reptiles. This study provides the first report and characterisation of amphibians and reptile communities across primary habitat types of the Victoria-Anepahan Mountain Range on Palawan Island along the western edge of the archipelago. A total of 41 amphibian and reptile species were recorded throughout our sampling sites (n = 27 species) or in targeted habitat searches (14 species). A species richness estimator predicted that 35 species may be present in our sampling sites, suggesting that a significant proportion of secretive species may continue to be unrecorded, especially for reptiles. Higher species richness was found in secondary growth than in mixed-use agricultural areas or even pristine forest. The low species richness recorded from pristine forest types may be due to these forests now being restricted to higher elevations where species diversity has been documented to decrease. Our results also show that complex community structures (species assemblages) are to be equally expected in both secondary growth and pristine forests. Together, our results show how species richness and community assemblages may vary across habitats, highlighting that old growth forest does not always support higher species richness, particularly in high elevations.